Redundant Capasitive Sensor untuk Pendeteksi Gelembung Udara Fault Tolerance - Basjaruddin, Noor Cholis (Transmisi, 2009)
Detection of air bubbles in the blood is important for various medical treatments that use Blood Extracorporeal Circuits (ECBC), such ashemodialysis, hemofiltration, and cardio pulmonary bypass. Therefore we need a reliable detection of air bubbles. In this research designed capasitive redundant sensors for detecting air bubbles fault tolerance. A Triple Modular Redundancy (TMR) method is used to select the output capacitor of the three sensors mounted on the blood hose. TMR module will choose the middle of three sensors output value. Application of TMR will prevent errors in the detection of air bubbles resulting from the failure of the sensor. Keywords: air bubble detection, triple modular redundancy (TMR) , extracorporeal blood circuits